FASE PENERIMAAN KEHILANGAN PASANGAN BERDASARKAN WAKTU DAN JENIS KELAMIN - Rahmawati, Rahmawati; Agus Ari Afandi, Agus Ari Afandi; Ahmad Maftukhin, Ahmad Maftukhin (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2019)
Loss is a state of an individual who parted with something that previously existed then becomes non-existent, either partly or entirely. A person who left a family member suddenly will cause a mental shock. The purpose of this study is to analyze the difference in the phase of loss of the sex partner in Cancung Village.The research method used analytical with cross sectional approach. Data obtained from interviews using a questionnaire, a population of 114 elderly in the village of Cancung. Sample 58 consisted of 45 women and 13 men. Sampling technique in this study Simple Random Sampling and presented in cross tabulation with statistical test chi-square test with a value of 0.05The results showed that most of the elderly men and women had reached the acceptance pace in men 11 (84.6%), in women 40 (88.9% while at the time of admission lost more than half the elderly women experienced the time of admission long term 31 (68,8%) mean while men respondent more than partially had acute acceptance time 9 (69,24%) From result of statistical test Chi-Square test got p value 0.002 <a = 0.05, Thus H1 is received, it means there is a difference phase of loss of pairs by time and gender, obtained p = 0.013 <a = 0.05.Thus H1 received, it means there is a difference in the phase loss of the pair based on time and sex.It is important for families to accompany elderly families with attention to the phases of acceptance of loss of spouses to be passed by the elderly